2022
DOI: 10.3390/ijms231710121
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Transcriptome and Metabolome Reveals Distinct Responses of Pelteobagrus fulvidraco against Aeromonas veronii Infection at Invaded and Recovering Stage

Abstract: Yellow catfish (Pelteobagrus fulvidraco) is an important aquaculture fish susceptible to Aeromonas veronii infection, which causes acute death resulting in huge economic losses. Understanding the molecular processes of host immune defense is indispensable to disease control. Here, we conducted the integrated and comparative analyses of the transcriptome and metabolome of yellow catfish in response to A. veronii infection at the invaded stage and recovering stage. The crosstalk between A. veronii-induced genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 85 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…9A, 98.6% and 82.9% respective explanatory degrees obtained indicate that the model is well constructed. In the plot, farther distance of the microbiota from the origin point was correlated with closer association with the metabolites and vice versa .62 A positive or negative loading value indicates a positive or negative association with another group; the larger the absolute value of the loading value, the stronger the association. Our results showed that there is strong correlation between the two omic data sets.…”
Section: Resultsmentioning
confidence: 98%
“…9A, 98.6% and 82.9% respective explanatory degrees obtained indicate that the model is well constructed. In the plot, farther distance of the microbiota from the origin point was correlated with closer association with the metabolites and vice versa .62 A positive or negative loading value indicates a positive or negative association with another group; the larger the absolute value of the loading value, the stronger the association. Our results showed that there is strong correlation between the two omic data sets.…”
Section: Resultsmentioning
confidence: 98%
“…Microbiome analyses have revealed changes in the microbial community composition in the intestines of infected fish, serving as biological markers for disease ( 14 18 ). Recent advances in metabolomic analyses have also identified several potential chemical markers in pathogen-infected fish ( 19 23 ). However, these studies have the disadvantage of being invasive owing to the use of tissue or plasma for analysis, and the results reflect only the status of the individual examined, not the entire fish population in the culture tank.…”
Section: Introductionmentioning
confidence: 99%
“…Genes up-regulated, and probably involved in the fish immunity against bacteria, were found to relate to phagosome, Th1, and Th2 cell differentiation, complement and coagulation cascades, hematopoietic cell lineage, antigen processing and presentation, and cytokine–cytokine receptor interaction pathways, thus highlighting the role of inflammatory cytokines (IL-1β, IL-6, IL-11, IL-12, IL-35, and TNF) and chemokines (CXCL8 and CXCL13). Ning et al [ 12 ] performed a transcriptomic and metabolomic study in the yellow catfish ( Pelteobagrus fulvidraco ) against A. veronii . During infection, fish tended to increase the synthesis of lipids and to induce the inflammatory response, ROS production, and cell apoptosis while reducing the mitotic potential.…”
mentioning
confidence: 99%